SIMULASI PERHITUNGAN HIGH POWER AMPLIFIER PADA SISTEM VSAT - Indri Neforawati; Hoga Saragih (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2009)
Arithmatical simulation of High Power Amplifier (HPA) on VSAT system is a program which used  to calculate the capacity of HPA as a working test of maximum power on each remote station of the VSAT network system, afterward  can be obtained the available  capacity value and power capacity used, therefore  able to reallocate residual power below its available power spare. VSAT system can be used for several telecommunication application such as video broadcast, data broadcast,audio broadcast, banking operation, ATM and others. Due to the easy operational, maintanance and its instalment, VSAT system is more prifitable compare to ordinary terestrial band, its capability for  multiservice application become more  flexible in using  its network. The software used is Visual Basic 6.0 version and database Microsoft Access. These software take a role as visualization and planning for remote station development and also power capasity needed for each remote in the calculation of HPA.